1998
DOI: 10.1084/jem.188.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Complement-dependent Proinflammatory Properties of the Alzheimer's Disease β-Peptide

Abstract: Large numbers of neuritic plaques (NP), largely composed of a fibrillar insoluble form of the β-amyloid peptide (Aβ), are found in the hippocampus and neocortex of Alzheimer's disease (AD) patients in association with damaged neuronal processes, increased numbers of activated astrocytes and microglia, and several proteins including the components of the proinflammatory complement system. These studies address the hypothesis that the activated complement system mediates the cellular changes that surround fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
192
1
8

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(213 citation statements)
references
References 33 publications
12
192
1
8
Order By: Relevance
“…Although secretion of C1q and C5 could not be demonstrated, since other cells in the microvascular environment, including macrophages/microglia, can secrete these proteins (Walker, 1998, unpublished data), there is the potential for all complement proteins to be produced in the localized microvascular environment. The strongly increased secretion of C3 by HCSMC following Aβ stimulation is of significance as this is a pivotal protein in both the classical and alternative activation pathways of the complement cascade (Bradt et al, 1998). Markers for complement activation have now been found in many neurodegenerative diseases or where brain injury has occurred (Barnum, 2002;van Beek et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although secretion of C1q and C5 could not be demonstrated, since other cells in the microvascular environment, including macrophages/microglia, can secrete these proteins (Walker, 1998, unpublished data), there is the potential for all complement proteins to be produced in the localized microvascular environment. The strongly increased secretion of C3 by HCSMC following Aβ stimulation is of significance as this is a pivotal protein in both the classical and alternative activation pathways of the complement cascade (Bradt et al, 1998). Markers for complement activation have now been found in many neurodegenerative diseases or where brain injury has occurred (Barnum, 2002;van Beek et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ peptide can activate the classical complement pathway by binding C1q in the absence of specific antibodies (Rogers et al, 1992;Webster et al, 1997), as well as activating the alternative complement pathway in the absence of C1q (Bergamaschini et al, 1999;Bradt et al, 1998). Studies have shown localized expression of different complement mRNAs within the brain (Johnson et al, 1992;Walker and McGeer, 1992), with significant increases of complement mRNA expression in brain regions selectively affected by AD (Yasojima et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…One common disease exemplifying this idea is Alzheimer's disease, in which the accumulation of extracellular A␤ peptide contributes to the pathogenesis (Hardy and Selkoe, 2002). Aggregated A␤ peptide can activate both the classical and alternative complement cascades in vitro by binding C1q and C3b, respectively (Jiang et al, 1994;Bradt et al, 1998); this is likely to be the trigger of sequential activation of these pathways, resulting in the formation of C5b, the initial component of the membrane attack pathway, thereby leading to the deposition of the MAC evident in Alzheimer's disease brains (McGeer et al, 1989;Itagaki et al, 1994;Webster et al, 1997;Yasojima et al, 1999). Interestingly, the binding of A␤ peptide by C3b likely promotes its phagocytosis and removal, because the transgenic overexpression of an inhibitor of C3b formation increases A␤ peptide accumulation in mice expressing the human amyloid precursor protein (WyssCoray et al, 2002); importantly, the increased A␤ peptide deposition is accompanied by enhanced neurodegeneration in these mice (Wyss-Coray et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The immune system also appears to participate in AD pathogenesis (7)(8)(9)(10)(11). Moreover, immune-based strategies have been shown to be effective in clearing A␤ from the brains of APP transgenic (Tg) mice (12)(13)(14)(15).…”
mentioning
confidence: 99%